Pembentukan Peraturan Daerah Tentang Rencana Tata Ruang Wilayah (RTRW) Provinsi Riau: Dinamika dan Permasalahannya - Suparto Suparto (Jurnal Selat, 2019)
Regional Regulation (Perda) is a regulation made by the Regional Head together with the DPRD that fulfills the elements of welfare and usefulness of a region. One of the Regional Regulations that has a strategic function is the Regional Regulation on Regional Spatial Planning (RTRW) because that is where land allocation is in accordance with the functions of the area regulated. However, the drafting of the RTRW Regional Regulation is not easy to differ from other local regulations because many interests must be considered and accommodated in its compilation including the drafting of the Riau Province RTRW Perda. After going through a very long process, the establishment of regional regulations was finally determined by The Governor of Riau, namely Regional Regulation Number 10 Year 2018 concerning the Riau Province Regional Spatial Plan with the following details: (1). Cultivation Area = 8,067,344 ha. (2). Protected area covering an area of ​​945,532 ha, with a total area of ​​9,012,886 ha. Although the Regional Regulation concerning the Riau Province RTRW has been established, there are still problems that must be resolved, namely concerning the emptying of areas that have become oil palm plantations in forest areas. This is not an easy job because it has to cut down oil palm trees with an area of ​​hundreds of thousands of hectares. Based on Law Number 12 Year 2011 there is no difference between the Provincial RTRW Perda and other Perda or having the same position both in terms of position and formation procedures. Whereas in the process of establishing a Provincial Regional Spatial Planning Regulation involving many agencies and ministries, among others, the Ministry of Home Affairs, the Ministry of Environment and Forestry, the Ministry of National Development Planning/BAPPENAS, the Ministry of Agriculture and Spatial Planning and the Geospatial Information Agency.